2022
DOI: 10.3390/horticulturae8020152
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilization of Growing Media: Response of N Mineralization to Temperature and Moisture

Abstract: Managing plant fertilization is a major concern of greenhouse growers when it comes to sustainable production on growing media. Organic fertilization is popular, but more difficult to control since organic compounds first need to be mineralized by microbes. The objective of this study was to characterize the time course of N mineralization by different fertilizer–growing media pairs, in the absence of plants. Several incubations were carried out at four temperatures (4, 20, 28, and 40 °C) and three suction pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…N mineralization in different GM types is fully described in Cannavo et al (2022), where temperature and moisture effects are quantified, and the mechanisms of regulation of nitrogen mineralization are discussed. We showed that in 49 days, 25%-70% of the fertilizers were mineralized at the temperature of 20 or 28 • C, depending on the GMs and the fertilizers, and that the mineralization plateau could be reached from 28 days of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…N mineralization in different GM types is fully described in Cannavo et al (2022), where temperature and moisture effects are quantified, and the mechanisms of regulation of nitrogen mineralization are discussed. We showed that in 49 days, 25%-70% of the fertilizers were mineralized at the temperature of 20 or 28 • C, depending on the GMs and the fertilizers, and that the mineralization plateau could be reached from 28 days of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…The fertilizer compositions are presented in Table 2, but their commercial names were kept confidential. The experimental design for collecting the dataset is fully described in Cannavo et al (2022).…”
Section: Origin Of the Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The application of organic fertilisation is complex because organic compounds first need to be mineralised. Cannavo et al [10] reported that the release of mineral N is strongly dependent on the growing media, temperature, humidity, and fertiliser used. However, as the results described in this study were only derived from incubation trials, they should be additionally verified using plant experiments.…”
Section: Special Issue Overview and A Short Discussionmentioning
confidence: 99%